Fungal plant pathogenesis mediated by effectors - De Wit, P.; Testa, A.; Oliver, Richard (2016)
The interactions between fungi and plants encompass a spectrum of ecologies ranging from saprotrophy (growth on dead plant material) through pathogenesis (growth of the fungus accompanied by disease on the plant) to symbiosis (growth of the fungus with growth enhancement of the plant). We consider pathogenesis in this article and the key roles played by a range of pathogen-encoded molecules that have collectively become known as effectors.